1978
DOI: 10.1017/s0014479700008334
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Systematic Spacing Design as an Aid to the Study of Inter-cropping: Some General Considerations

Abstract: Assessment of the relative advantages or otherwise of inter-cropping compared with sole cropping needs to be done over a wide range of plant populations. Systematic spacing designs lend themselves to this, and the paper discusses the interpretation of the yield/plant population curves which can be so derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…In the past, there has been debate regarding planting density and plant spacing when calculating LER for comparing monocultures with mixed cropping systems (Oyejola and Mead, 1982). Optimum plant densities in monoculture have been suggested for best achievable yields (Huxley and Maingu, 1978), and deviation from these planting densities will reduce the yield of the monocultures and thus bias LER toward the mixed plantings. However, in some instances when certain variables are being isolated it is appropriate to maintain similar densities across treatments (Mead and Willey, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, there has been debate regarding planting density and plant spacing when calculating LER for comparing monocultures with mixed cropping systems (Oyejola and Mead, 1982). Optimum plant densities in monoculture have been suggested for best achievable yields (Huxley and Maingu, 1978), and deviation from these planting densities will reduce the yield of the monocultures and thus bias LER toward the mixed plantings. However, in some instances when certain variables are being isolated it is appropriate to maintain similar densities across treatments (Mead and Willey, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Here in additive intercropping of maize and soybean, the intercropped soybean grain yield per hectare was reduced by 40% as compared sole cropped (Table 4). Comparably, Huxley and Maingu (1978), in cereals and legumes intercropping system, reported that the grain yield of the legume component declined, on average, by about 52% of the sole crop yield, whereas the cereal yield was reduced by only 11%.…”
Section: Soybean Yield Components and Yieldmentioning
confidence: 93%
“…Ofori & Stern (1987) reported that the cereal components of cereal-legume intercrops were the more competitive species due to a relatively higher growth rate, a height advantage and a more extensive rooting system . Huxley & Maingu (1978) referred to the cereal as the dominant crop and the legume as the dominated component . Francis (1985) proposed that to reduce the size and cost of yield tests it is useful to identify a single variety of the dominant crop (which is generally less affected by the variety of the dominated species) and test several legume genotypes in order to identify higher-yielding varieties of the dominated component .…”
Section: Introductionmentioning
confidence: 99%